Seven Plus One Steps to Assess Pigmented Nail Bands (Melanonychia Striata Longitudinalis) - Aimilios Lallas; Katarzyna Korecka; Zoe Apalla; Dimitrios Sgouros; Konstantinos Liopyris; Giuseppe Argenziano; Luc Thomas (Mattioli1885, 2023)
Melanonychia striata longitudinalis might involve one or more fingers and/or toes and might result from several different causes, including benign and malignant tumors, trauma, infections, and acti-vation of melanocytes that might be reactive or related to the pigmentary trait,drugs and some rare syndromes.This broad differential diagnosis renders the clinical assessment of melanonychia striata particularly challenging. Nail matrix melanoma is relatively rare, occurs almost always in adults in-volves more frequently the first toe or thumb.The most common nail unit cancer,squamous cell carcinoma / Bowen disease (SCC) of the nail matrix is seldom pigmented. Histopathologic examina-tion remains the gold standard for melanoma and SCC diagnosis,but excisional or partial biopsies from the nail matrix require training and is not routinely performed by the majority of clinicians.Furthermore, the histopathologic evaluation of melanocytic lesions of the nail matrix is particularly challenging, since early melanoma has only bland histopathologic alterations. Dermatoscopy of the nail plate and its free edge significantly improves the clinical diagnosis, since specific patterns have been associated to each one of the causes of melanonychia. Based on knowledge generated and pub-lished in the last decades, we propose herein a stepwise diagnostic approach for melanonychia striata longitudinalis: 1) Hemorrhage first 2) Age matters 3) Number of nails matters 4) Free edge matters 5) Brown or gray? 6) Size matters 7) Regular or irregular and, finally,"follow back".